Basic psychological needs as a predictor of positive affects: a look at peace of mind and vitality in Chinese and American college students. Issue 4 (3rd July 2020) - Yu, Shi; Zhang, Fengjiao; Nunes, Ludmila D.; Deng, Yanhe; Levesque-Bristol, Chantal
ABSTRACT: Research in the past decade has shown basic psychological needs (BPNs) as essential for human wellness, but little is known about their effects on positive affects that are more characteristic of East Asian cultures or whether their effects differ for different affective outcomes. We examined the role of BPNs in a recently conceptualized affect characteristic of East Asians, namely, peace of mind (PoM). We also investigated whether this effect differs from that on vitality, a high-arousal affect more characteristic of American culture. Furthermore, we examined whether these relationships are moderated by culture. Key findings include: (1) BPNs positively predict PoM; (2) PoM is positively correlated with vitality, while the effect of BPNs is stronger on PoM than on vitality; (3) PoM (relative to vitality) is more characteristic of Chinese than American college students; and (4) culture does not moderate the relative effect of BPNs on PoM vs. vitality.